Legal Study on Human Rights Protection in Cases of Violence against Women and Children - Abrori, Abrori (Science Tech Group, 2025)
This article examines the evolution, implementation, and challenges of human rights protection frameworks for women and children who experience violence. Despite significant advancements in international human rights law and domestic legislation, violence against women and children remains pervasive globally, indicating a troubling gap between legal protections and practical realities. Through qualitative descriptive research utilizing a library research approach, this study analyzes the effectiveness of current legal frameworks, identifies implementation barriers, and explores promising practices. The research reveals systemic challenges including insufficient enforcement mechanisms, persistent sociocultural barriers, limited access to justice, and inadequate victim support services. The study concludes that effective protection requires a comprehensive approach combining robust legal frameworks with cultural transformation, institutional accountability, and community engagement. Recommendations include strengthening enforcement mechanisms, addressing cultural and institutional barriers, expanding victim-centered support systems, and enhancing data collection and monitoring protocols.